BOOMERANG EFFECT DALAM TOLERANSI PADA AKUN INSTAGRAM HABIB JAFAR (@husein_hadar) - Sekar Alifah Binar Fadila; Nasichah, Mifta Hul Zanah, Nida Nadia Najla Mawaddah (ADISAM PUBLISHER, 2024)
Social media such as Instagram has become a major platform for communication and information dissemination. Habib Jafar, a young preacher, actively uses Instagram to spread messages of tolerance and peace. However, the message of tolerance conveyed by Habib Jafar is often not well received by everyone and can cause the opposite reaction known as the boomerang effect.This research uses a qualitative descriptive approach with content analysis techniques to investigate how Habib Jafar's Instagram posts can trigger a boomerang effect in the context of intolerance. Data was obtained from Habib Jafar's Instagram account by taking a sample of 9 posts that had high interaction. Through direct observation, documentation and content analysis, this research identified the main themes and patterns of user responses to the messages of tolerance and diversity conveyed by Habib Jafar.